2008
DOI: 10.1590/s0482-50042008000300002
|View full text |Cite
|
Sign up to set email alerts
|

A importância da intervenção nutricional na redução do peso corpóreo em pacientes com síndrome do anticorpo antifosfolípide

Abstract: ResumoObjetivo: Avaliar a eficácia da intervenção nutricional na redução do excesso de peso (EP), em pacientes com síndrome do anticorpo antifosfolípide (SAF). Métodos: Incluídos 40 pacientes, acima de 18 anos, com diagnóstico de SAF primária ou secundária, acompanhados no Serviço de Reumatologia do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo (HC-FMUSP) e recrutados no período de outubro de 2005 a fevereiro de 2006. Foram coletados dados demográficos e realizados a revisão de pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
2
0
4
Order By: Relevance
“…This concern with the nutritional status of the patient is, in turn, even more valued in the course of a pregnancy due to the risk of maternal and fetal complications that obesity can cause. Considering such losses, this is one of the main risk factors that must be fought in individuals with APS [ 38 , 39 ]. A study by Caldas et al showed worse prognosis in obese patients with primary APS compared with those who were not obese.…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concern with the nutritional status of the patient is, in turn, even more valued in the course of a pregnancy due to the risk of maternal and fetal complications that obesity can cause. Considering such losses, this is one of the main risk factors that must be fought in individuals with APS [ 38 , 39 ]. A study by Caldas et al showed worse prognosis in obese patients with primary APS compared with those who were not obese.…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…Klack and Carvalho evaluated the efficacy of nutritional intervention in the treatment of overweight in 40 APS patients treated at least after 2 months and had positive results in the adequacy of body weight in these patients, indicating the nutritional intervention as a first choice in obese individuals with APS [ 39 ].…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…Essa redução ponderal melhora a tolerân-cia à glicose e o perfil lipídico, reduz os níveis de pressão arterial e os sintomas associados a doenças degenerativas articulares, depressão e apneia do sono, além de melhorar os escores que avaliam a qualidade de vida 23 .…”
Section: I S C U S S ã Ounclassified
“…Dentre as investigadas temos a tireoidopatia, a Hipertensão arterial sistêmica (HAS), diabetes mellitus e pré-eclâmpsia, onde apresentam alto risco para perdas obstétricas. Apesar de existirem várias pesquisas sobre os fatores de risco para a SAF, ainda vemos a exclusão de alguns determinantes de saúde da sociedade atual, um deles a obesidade, que é o acúmulo de gordura corporal onde pode acarretar várias situações que desencadeiam a disfuncionalidade no organismo, principalmente no sistema cardiocirculatório (Klack & Carvalho, 2008).…”
Section: Resultsunclassified